IFN-gamma-dependent activation of macrophages during experimental infections by Mycobacterium ulcerans is impaired by the toxin mycolactone - Torrado, Egídio (2010)
Buruli ulcer, caused by Mycobacterium ulcerans infections, is a necrotizing skin disease whose pathogenesis is associated with the exotoxin mycolactone. Despite the relevance of this emergent disease, little is known on the immune response against the pathogen. Following the recent demonstration of an intramacrophage growth phase for M. ulcerans, we investigated the biological relevance of IFN-gamma and the antimycobacterial mechanisms activated by this cytokine in M. ulcerans-infected macrophages. Three M. ulcerans strains were tested: 5114 (mutant mycolactone-negative, avirulent strain); 94-1327 (intermediate virulence); and 98-912 (high virulence). We show in this study that IFN-gamma is expressed in mouse-infected tissues and that IFN-gamma-deficient mice display increased susceptibility to infection with strains 5114 and, to a lesser extent, 94-1327, but not with the highly virulent strain. Accordingly, IFN-gamma-activated cultured macrophages controlled the proliferation of the avirulent and the intermediate virulent strains. Addition of mycolactone purified from strain 98-912 to cultures of IFN-gamma-activated macrophages infected with the mycolactone-negative strain led to a dose-dependent inhibition of the IFN-gamma-induced protective mechanisms, involving phagosome maturation/acidification and increased NO production, therefore resulting in increased bacterial burdens. Our findings suggest that the protection mediated by IFN-gamma in M. ulcerans-infected macrophages is impaired by the local buildup of mycolactone.